2016
DOI: 10.1128/jvi.00322-16
|View full text |Cite
|
Sign up to set email alerts
|

Both Epistasis and Diversifying Selection Drive the Structural Evolution of the Ebola Virus Glycoprotein Mucin-Like Domain

Abstract: Throughout the last 3 decades, Ebola virus (EBOV) outbreaks have been confined to isolated areas within Central Africa; however, the 2014 variant reached unprecedented transmission and mortality rates. While the outbreak was still under way, it was reported that the variant leading up to this outbreak evolved faster than previous EBOV variants, but evidence for diversifying selection was undetermined. Here, we test this selection hypothesis and show that while previous EBOV outbreaks were preceded by bursts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 54 publications
3
21
0
Order By: Relevance
“…With this good statistical behavior, further analyses of independent influenza data sets showed a consistent pattern: (i) many pairs of correlated sites are involved in epistatic interactions, (ii) these pairs of sites form extensive networks of sites, consistent with Poon et al (2007b), but that are also affected by substitutions that occur sequentially -showing evidence for historical contingency in fast-evolving organismsand (iii), more intriguingly, that these epistatic pairs of sites form long-range spatial interactions. This latter point precludes the idea of a close physical link as in the case of tRNA molecules (Kimura, 1985;Chen et al, 1999), so that these long-range interactions must bring about stability (Thomas et al, 2010) and/or conformational (Mitraki et al, 1991;Newcomb et al, 1997;Harms and Thornton, 2014) and/or functional changes, as in the case of the M2 data set or in the case of the Ebola virus (Ibeh et al, 2016). While there is evidence that epistasis can be prevalent in RNA viruses (at least 31% in (Shapiro et al, 2006)) and in bacteria (15% in (Weinreich et al, 2006)), it is not impossible that epistasis reflects an evolutionary constraint stronger in RNA viruses than in organisms with larger and more redundant genomes: because these viruses have a small genome, mutations are expected to have large fitness effects, which can be alleviated by compensatory mutations (Sanjuán and Elena, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…With this good statistical behavior, further analyses of independent influenza data sets showed a consistent pattern: (i) many pairs of correlated sites are involved in epistatic interactions, (ii) these pairs of sites form extensive networks of sites, consistent with Poon et al (2007b), but that are also affected by substitutions that occur sequentially -showing evidence for historical contingency in fast-evolving organismsand (iii), more intriguingly, that these epistatic pairs of sites form long-range spatial interactions. This latter point precludes the idea of a close physical link as in the case of tRNA molecules (Kimura, 1985;Chen et al, 1999), so that these long-range interactions must bring about stability (Thomas et al, 2010) and/or conformational (Mitraki et al, 1991;Newcomb et al, 1997;Harms and Thornton, 2014) and/or functional changes, as in the case of the M2 data set or in the case of the Ebola virus (Ibeh et al, 2016). While there is evidence that epistasis can be prevalent in RNA viruses (at least 31% in (Shapiro et al, 2006)) and in bacteria (15% in (Weinreich et al, 2006)), it is not impossible that epistasis reflects an evolutionary constraint stronger in RNA viruses than in organisms with larger and more redundant genomes: because these viruses have a small genome, mutations are expected to have large fitness effects, which can be alleviated by compensatory mutations (Sanjuán and Elena, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…While previous work showed that both diversifying selection and correlated evolution can affect the same gene and even the same site in a viral genome such as Ebola’s (Ibeh et al ., 2016), a ssRNA virus, the generality of this association is still unknown. At the gene level, we found strong heterogeneity among all four viral types for gene numbers showing evidence for selection, correlated evolution or both ( X 2 = 206.54, df = 6, P < 2.2×10 −16 ).…”
Section: Resultsmentioning
confidence: 99%
“…This last point suggests that a seldom explored evolutionary process, correlated evolution, might play a key role in the evolution of these single-stranded viruses. Indeed, recent work uncovered pervasive evidence for correlated evolution in influenza viruses (Nshogozabahizi et al ., 2017), and both the Zika (Aris-Brosou et al ., 2017) and the Ebola viruses (Ibeh et al ., 2016), with evidence in the latter that sites evolving in a correlated manner can also be under episodic diversifying selection. However, this recent body of evidence is so far limited to a small number of ssRNA viruses, so that the combined role of correlated evolution and selection is difficult to generalize.…”
Section: Introductionmentioning
confidence: 99%
“…The constraining effects of larger and smaller beneficial mutational neighborhoods were elegantly demonstrated in 6 by Burch and Chao, who noted that the high mutation rate of 6 was not sufficient to allow constrained genotypes to traverse a rugged fitness landscape (33). The ruggedness of viral fitness landscapes has been demonstrated for many viruses, including HIV (31), influenza virus A (34,35), and Ebola virus (36), and the phenomenon of mutational neighborhoods constraining evolutionary trajectories has been demonstrated in cellular organisms as well (37)(38)(39). Many of these studies involved prolonged experimental evolution, whereas our study used a very narrow window of lethal selection: a single night's selection on a novel host.…”
Section: Discussionmentioning
confidence: 99%